Kualitas Pelayanan Aplikasi Mobile JKN di BPJS Kesehatan Kota Tangerang - Adzani, Shaylika Hafana; Arenawati (Jurnal Administrasi Karya Dharma, 2025)
This study aims to analyze the quality of public services through the Mobile JKN application provided by BPJS Kesehatan in Tangerang City using the e-Service Quality theory by Papadomichelaki and Mentzas, which includes four dimensions: Efficiency, Trust, Reliability, and Citizen Support. The research method used is quantitative with a descriptive approach. Data was collected through questionnaires distributed to 270 respondents, determined using the Isaac and Michael formula. The analysis was conducted using SPSS 25 for Windows. The findings show that the service quality of the Mobile JKN application is generally considered good, with each indicator scoring above the minimum threshold of 65%. The Trust indicator received the highest percentage at 80%, followed by Citizen Support at 79%, Efficiency at 78%, and Reliability at 76%. These results indicate that users have a positive perception of the service quality of the Mobile JKN application in Tangerang City, particularly in terms of security, ease of use, service responsiveness, and public support. Despite these favorable results, several issues such as login difficulties, data verification, and limited digital literacy among users suggest the need for further improvements in technical performance and user education. This research highlights the importance of continuous innovation and effective digital service delivery to enhance public satisfaction and strengthen good governance in public health services.